Digital Governance and Citizen Trust: Analyzing the Efficacy of E-Government Services in Mitigating Administrative Corruption in Southeast Asia - Nasution, Nur Hakima Akhirani (International Journal of Educational Research Excellence (IJERE), 2025)
This study examines the relationship between digital governance implementation and administrative corruption reduction in Southeast Asia, focusing on how e-government services influence citizen trust and mitigate corrupt practices. Through qualitative analysis of eight Southeast Asian countries, this research explores the mechanisms through which digital transformation enhances transparency, accountability, and public participation in governance processes. The study employs in-depth interviews with government officials, civil society representatives, and citizens to understand the multifaceted impact of e-government initiatives on corruption reduction. Findings reveal that countries with higher E-Government Development Index (EGDI) scores demonstrate significantly lower corruption levels and enhanced citizen trust, with Singapore leading the region in both digital governance maturity and corruption perception scores. The research identifies key success factors including robust ICT infrastructure, comprehensive digital literacy programs, and strong institutional frameworks that support transparent governance practices. However, challenges persist in bridging the digital divide and ensuring equitable access to digital services across socioeconomic groups. The study concludes that while e-government services demonstrate substantial potential for reducing administrative corruption, their effectiveness depends critically on contextual factors including political commitment, technological readiness, and citizen engagement levels. These findings contribute to the growing body of literature on digital governance and provide practical insights for policymakers seeking to leverage technology for anti-corruption efforts in developing nations